WATERSHED DEVELOPMENT IN HOTGI VILLAGE - MS. S.M. PAWAR; PROF. P.A. HANGARGEKAR; PROF. S.C. WADANE (International Journal of Innovations in Engineering Research and Technology, 2021)
Hotgi is a small village in Solapur district of state of Maharashtra. It is facing acute water scarcity problem due to insufficient rainfall every year.Thewatershed area recharging capacity of watershed is about 89.20% of water available forrecharge.Total water to be conserved using Farm pond, Check dam,Vanraibandhara, Rain water harvesting, Nalabunding is 1197344m3 per year.Total cost for all these structuresare estimated as61,95,260/-